2014
DOI: 10.1111/jcmm.12242
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA‐99a attenuates heart remodelling and improves cardiac performance after myocardial infarction

Abstract: MicroRNAs are involved in the regulation of various cellular processes, including cell apoptosis and autophagy. Expression of microRNA-99a (miR-99a) is reduced in apoptotic neonatal mice ventricular myocytes (NMVMs) subjected to hypoxia. We hypothesize that miR-99a might restore cardiac function after myocardial infarction (MI) by up-regulation of myocyte autophagy and apoptosis. We observed down-regulated miR-99a expression in NMVMs exposed to hypoxia using TaqMan quantitative reverse transcriptase-polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 42 publications
1
59
0
1
Order By: Relevance
“…Mounting literatures have proved that miRNAs are involved in multiple diseases including MI [11-13]. A previous study has reported miRNA (miR)-99a alleviates heart remodeling and improves cardiac performance after MI [14]. Another study illustrated circulating miR-1 acts as a novel biomarker for MI [15].…”
Section: Introductionmentioning
confidence: 99%
“…Mounting literatures have proved that miRNAs are involved in multiple diseases including MI [11-13]. A previous study has reported miRNA (miR)-99a alleviates heart remodeling and improves cardiac performance after MI [14]. Another study illustrated circulating miR-1 acts as a novel biomarker for MI [15].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with a former study on the protective role of miR-99 against cardiomyocyte apoptosis. 17) Thus, miR-99a has protective effects against cardiomyocyte oxidative injury.…”
Section: Discussionmentioning
confidence: 99%
“…15,16) However, in a model of myocardial infarction, miR-99a has been revealed to inhibit cardiomyocyte apoptosis, suggesting a cardioprotective role for miR-99a. 17) These studies lead us to speculate about the role of miR-99a in oxidative injury during cardiovascular disease, however, little has been reported in previous studies.…”
Section: Editorial P310mentioning
confidence: 99%
“…Searching for direct target genes of miR-99a in cardiomyocytes will advance our understanding of the mechanisms whereby miR-99a protects cardiomyocytes from oxidative injury. Recent studies demonstrated that overexpression of miR-99a in murine hearts using a lentiviral vector attenuated left ventricular remodeling after myocardial infarction, 30) and cardiac hypertrophy induced by transverse aortic constriction. 31) Further studies are necessary to determine whether overexpression of miR-99a also attenuates LPS-induced myocardial oxidative injury and dysfunction without altering physiological ROS signaling in a A number of miRNAs have been identified that are expressed in cardiac tissue and thus likely to play a key role in cardiac physiology and pathophysiology.…”
Section: Article P422mentioning
confidence: 99%